Carotid web: an under-recognized and misdiagnosed ischemic stroke etiology. (15th March 2021) - Osehobo, Ehizele M; Nogueira, Raul G; Koneru, Sitara; Al-Bayati, Alhamza R; de Camara, Catarina Perry; Nahab, Fadi; Liberato, Bernardo; Frankel, Michael R; Allen, Jason W; Park, Charlie Chulhyun; Haussen, Diogo C
Abstract : Background: Carotid web (CaW) constitutes a possible cause of ischemic stroke, particularly large vessel occlusion syndromes. We aim to evaluate misdiagnosis rates and diagnosis trends for CaW. Methods: Based on CT angiography (CTA), we prospectively identified a cohort of patients with symptomatic CaW treated at two comprehensive stroke centers (CSC) from 2014 to 2020 to assess misdiagnosis. Official CTA reports from the CSCs and referring hospitals were then reviewed for mention of CaW. For diagnosis trends, we retrospectively analyzed a CSC electronic medical record, identifying patients with CaW mentioned in an official CTA report from 2011 to 2020. Results: For misdiagnosis, 56 patients with symptomatic CaW were identified in the CSCs; 16 (28%) had bilateral CaW, totaling 72 CaWs. Only one CaW (5.5%) was reported at referring facilities, from 14 patients/18 CaWs imaged with CTA. Conversely, 43 (69%) CaWs were reported from 49 patients/62 CaWs at the CSC (p<0.01). For diagnosis trends, from 2011 to 2020, 242 patients at a CSC accounted for 266 CTA reports mentioning CaW. The majority of these reports (n=206, 77%) were associated with stroke/transient ischemic attack (TIA) ICD-9/ICD-10 codes. The rate of CaW diagnosis adjusted per 1000 patients with stroke/TIA increased over time, 2015 being the most significant point of change ('joinpoint'; p=0.01). The analysis of CaW mentions normalized per 1000 CTA reports also showed increasing rates of diagnosis over time (joinpoint:2014; p<0.02). Conclusion: CaW was predominantly identified in patients with strokes/TIAs rather than asymptomatic patients. CaW was commonly overlooked in facilities with lower levels of cerebrovascular certification. Recognition of CaW at a CSC has significantly increased over time, independent of overall imaging and stroke patient volume.